Pengaruh Pengawasan dan Akuntabilitas terhadap Penerapan Anggaran Berbasis Kinerja pada SKPD di Kabupaten Gorontalo - Nurul Aulia Hasan; Mattoasi, Mattoasi; Monoarfa, Valentina Monoarfa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is related to the implementation of performance-based budgeting, so it is hoped that each use of the budget is in accordance with the organization's strategy, namely the organization's vision. The variable that is thought to have an influence on performance-based budget standards is the existence of elements of supervision and accountability. The method used is a quantitative method in measuring the influence of exogenous variables on indigenous variables. The research results show that supervision and accountability, both partially and simultaneously, have a positive and significant effect of implementing performance-based budgeting in SKPD in Gorontalo Regency.